The Efficacy of Two Specific Toll-like Receptor 4 Antagonists (G2013 & M2000) in Clinical Inflammatory Disease - Taeb, Mahsa; Rahmani, Mehdi; Sharifi, Laleh; Mirshafiey, Abbas (British Journal of Healthcare and Medical Research, 2024)
Toll-like receptors (TLRs) are receptors of the innate immune system that detect pathogen-associated molecular patterns and endogenous “danger” molecules. Among the family, the fundamental role of Toll-like receptor 4 (TLR 4) has been underscored in the initiation of pro-inflammatory cellular signaling pathways. Therefore, the appropriate suppression of Toll-like receptor 4 signaling is vital to maintain the balance between autoimmunity and inflammatory responses to avoid detrimental effects caused by the host immune system. This paper reviewed the structure of TLRs and their essential role in inflammation, specifically Toll-like receptor 4, its signaling cascade, and its antagonists. Recently, using two new drugs, M2000 (β-D-Mannuronic acid) and G2013 (α-L-Guluronic acid), the novel Toll-like receptor 4 antagonists are proposed to control inflammatory conditions. Immunosuppressive and anti-inflammatory properties of M2000 and G2013 have been examined in invitro, pre-clinical, and clinical trial studies. Experimental and clinical studies on these drugs revealed TLR4 antagonistic properties with significant efficacy for controlling inflammatory responses and treating autoimmune diseases.